1996
DOI: 10.3892/or.3.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in patients with chronic obstructive pulmonary disease

Abstract: Abstract. Chronic obstructive pulmonary disease (COPD) is a relatively common disease, affecting mainly males in the western world. Although substantial data are available as regards the clinicopathological characterization of COPD, little is known of the molecular basis of the disease. In the present study we analysed the incidence of microsatellite instability (MI) in cytological specimens from patients with COPD. MI reflects increased mutational rate and is associated with decreased accuracy in the DNA repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The present authors have demonstrated genomic instability in the BL from a number of individuals with no clinical evidence of lung cancer, posing a question about exclusive occurrence of genomic instability in cancer. This observation was also supported by reports of genomic instability in nonmalignant diseases [117][118][119][120][121][122][123].…”
Section: Genomic Instabilitysupporting
confidence: 78%
“…The present authors have demonstrated genomic instability in the BL from a number of individuals with no clinical evidence of lung cancer, posing a question about exclusive occurrence of genomic instability in cancer. This observation was also supported by reports of genomic instability in nonmalignant diseases [117][118][119][120][121][122][123].…”
Section: Genomic Instabilitysupporting
confidence: 78%
“…Microsatellite DNA instability (MSI) has been initially reported in a number of human malignancies (5)(6)(7). During recent years such phenomena have also been detected in sputum cells of COPD patients, as well as in various other benign diseases (8)(9)(10)(11)(12). In addition, the detection of MSI in sputum cells of patients with COPD has been suggested to be disease specific in certain microsatellite markers, and could represent a useful marker of genetic susceptibility indicating destabilization of the genome at various loci (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that there are many genes with moderate effects in the pathogenesis of asthma rather than a few major ones. Chromosomal regions likely to harbour asthma susceptibility genes have been identified [8][9][10].…”
mentioning
confidence: 99%